(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
The purpose of this study is to describe the character of the main character in the book Kajao Laliddong The Great Thinker from the Bugis Land by Asmad Riady Lamallongeng and to describe the moral messages conveyed to the characters in the book Kajao Laliddong The Great Thinker from the Buginese Land. This qualitative study uses data methods which contain descriptive research methods. Descriptive research method is a study that aims to present information accurately and thoroughly about the very broad characteristics of a population. The data is also obtained from Library Research or literature studies. Literature study is a technique of collecting data using a review approach to books, notes, reports related to solving problems. The results of this study indicate that in the book of Kajao Laliddong the Great Thinker from Bugis Land, the main character has two types of characters, the first is a sanguine character (extrovert). There are seven types of sanguine characters related to the characters proposed by the Ministry of Education and Culture including caring, honest, logical thinking, social care, peace-loving, hard work and love for the homeland. Both, there are five types of choleric characters related to the types of characters proposed by the Ministry of Education and Culture, namely discipline, democracy, responsibility, creativity and hard work. The moral message conveyed by Kajao Laliddong in this book is about the soul of a king’s leadership. Social rules, the concept of pangadereng (customs) and which a king must apply and the humble character that a person must have.